2019
DOI: 10.1186/s12936-019-2751-9
|View full text |Cite
|
Sign up to set email alerts
|

Care-seeking behaviour and treatment practices for malaria in children under 5 years in Mozambique: a secondary analysis of 2011 DHS and 2015 IMASIDA datasets

Abstract: Background In Mozambique, the prevalence of malaria in children under 5 years of age is among the highest in the world, but limited data exist on determinants of care-seeking behaviour for malaria. This study aimed at determining the trends and factors associated with care-seeking behaviour for fever among children under 5 years of age and to assess the treatment practices for malaria. Methods Secondary data analysis of two cross-sectional studies. Descriptive statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
7
23
5
Order By: Relevance
“…It suggests the need for intensified social and behaviour change communication strategies to improve care-seeking efforts. The results are similar to what was reported in previous studies from Senegal and Mozambique, in which around onethird of children with fever did not receive any treatment or medical advice [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…It suggests the need for intensified social and behaviour change communication strategies to improve care-seeking efforts. The results are similar to what was reported in previous studies from Senegal and Mozambique, in which around onethird of children with fever did not receive any treatment or medical advice [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Moving on, this study nding on satisfaction with communication and interpersonal manner of care by the health providers supports the evidence that good communication between physicians and patients has a positive impact on patient satisfaction, thereby leading to improved compliance to treatment, decreased anxiety, increased recall and understanding of healthcare [33]. Also, the ndings of this study on the impact of socio-economic status on malaria satisfaction are consistent with the report from a nationwide study in Zambia, which showed some socio-economic status indices such as education, income and place of residence [34], as predictors of satisfaction with malaria care which contributed to the mothers' health-seeking behaviour [35].…”
Section: Discussionsupporting
confidence: 87%
“…In Mozambique, malaria is the leading cause of care-seeking, accounting for 45% of outpatient consultations and 24% of hospital admissions in 2015 [7]. The Mozambican Ministry of Health provides free diagnosis and treatment services for malaria at public health facilities [8], but these services require considerable human resource and health systems investment. Scarcity of resources and weak health system financing force the country to rely on international donors for the provision of RDTs and anti-malarial medicines, the majority of which are purchased by the US President’s Malaria Initiative and the Global Fund to Fight AIDS, Tuberculosis and Malaria.…”
Section: Introductionmentioning
confidence: 99%